MEDIA BERMAIN PANCING TERHADAP KEMAMPUAN MENGENAL KONSEP PADA ANAK TUNAGRAHITA RINGAN DI SLB - Munawarah, Yulia (Jurnal Pendidikan Khusus, 2017)
ABSTRACT Mild mentally retardation children of class I in SLB Siti Hajar Buduran Sidoarjo could not recognize the number concept yet. When the mild mentally retardation children were taught to recognize number 1 till 10 they could only mention well. The purpose of this research was to know the influence of playing fishing media toward recognizing number concept ability to mild mentally retardation childen in SLB Siti Hajar Buduran Sidoarjo. This research used quantitative approach and pre-experiment kind with research arrangement One Group Pre test Post test design. The research result indicated significant influence. It appeared from the children’s ability through the aspects of recognizing, mentioning, showing, sequencing, and matching number 1 till 10. This was proved by the result of data analysis which indicated that the value of z counted = 2,20 was greater than the value of z table = 1,96 it meant there was influence of playing fishing media toward recognizing number concept to mild mentally retardation children in SLB Siti Hajar Buduran Sidoarjo.   Keywords: Playing fishing media, recognizing number concept ability